Upaya Meningkatkan Hasil Belajar Matematika dengan Pendekatan Pendidikan Matematika Realistik (PMR) pada Siswa Kelas VI SDN Tanjung Duren Selatan 05 - Hilda Octaviani; Supardi U.S (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
The background of writing this is that the results of students' mathematics learning are still low in class VI SD. Students do more practice assignments and are less actively involved in the learning process. One alternative is to apply the application of Realistic Mathematics Education. The purpose of this study is to find out that the application of a Realistic Mathematics Education approach can help improve students' learning outcomes in mathematics. The method in this research is classroom action research. Instruments in this study, namely: the description test instrument and the non-test observation sheet instrument. The results of this study indicate that students' mathematics learning outcomes can be increased through the application of Realistic Mathematics Education. In cycle one, students' mathematics learning outcomes at the 1st meeting were 45% in the sufficient category and at the 2nd meeting it increased to 57% in the sufficient category. In the second cycle, the increase in students' mathematics learning outcomes at the 1st meeting was 60%, which was in the sufficient category, and at the 2nd meeting, the 85% increase was in the very good category. In the second cycle, there was a very good increase at the 2nd meeting. This can be categorized as a successful increase because it exceeds the minimum success indicator of 75% with KKM = 69 as a benchmark. The results of this study are expected to be useful to related parties who can use them, such as school principals, teachers, parents and students as well as future researchers.